Conceptualisation and framework for developing an educational program for caregivers of the elderly - Kloppers, Joan.M; Van Dyk, Agnes (International Journal of Medicine, 2016)
Most frequently, elderly are cared for in institutions by lay people. This can result in poor quality of care and neglect of the elderly. These caregivers lack skills and knowledge in the delivering of care for the elderly. The aim of the study was to do a situational analysis of the experiences of the elderly as well as the caregivers in respect of caring for the elderly in old age homes. The objective of the study were to explore and describe the experiences of the caregivers and the elderly with respect to caring for the elderly and nursing care they receive. A qualitative, explorative, descriptive, contextual and phenomenological design was used to perform this study. Themes were identified, as for example interpersonal relationship and communication (positive as well as negative). A Lack of in-service training for caregivers was revealed, as well as a lack of caring procedures, policies and guidelines. Staff shortages, were also identified. Out of these findings a conceptual framework was developed.